2022
DOI: 10.33102/2022249
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition and Sensory Preference of Beef Sausages with Unripe Jackfruit

Abstract: Underutilization of jackfruit and demand for healthier meat product with nutritional benefits and similar taste to meat had led to this study which to evaluate the proximate composition, and consumer preference of beef sausage with different ratio of unripe jackfruit.  Five formulations of beef sausage were prepared with different amount of beef to unripe jackfruit were: Control (65:0), A (48.75:16.26), B (32.5:32.5), C (16.25:48.75), and D (0:65).  Results found that carbohydrate contents of beef sausage with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Sensory evaluation is crucial in determining consumer acceptance of meat products [9]. For example, research on sausages with varying proportions of fish meat demonstrated that consumer preference decreased with higher fish content, particularly impacting factors like consistency, appearance, and tenderness [10]. Comprehending the multifaceted aspects of meat quality is essential for ensuring consumer satisfaction, optimising dietary value, and maintaining consistency across diverse product lines.…”
Section: Understanding Meat Qualitymentioning
confidence: 99%
“…Sensory evaluation is crucial in determining consumer acceptance of meat products [9]. For example, research on sausages with varying proportions of fish meat demonstrated that consumer preference decreased with higher fish content, particularly impacting factors like consistency, appearance, and tenderness [10]. Comprehending the multifaceted aspects of meat quality is essential for ensuring consumer satisfaction, optimising dietary value, and maintaining consistency across diverse product lines.…”
Section: Understanding Meat Qualitymentioning
confidence: 99%